Harmonization of Parking Fee Regulations in Local Regulations and Mayor's Regulations in the City of Yogyakarta - Anwar Hidayatulloh, bagus (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2024)
Abstract This research focuses on the investigation of the harmonization of parking regulations implemented in the city of Yogyakarta, including local regulations and those set by the mayor. The issues addressed encompass problems related to illegal parking and improper parking fee enforcement, which have the potential to create various challenges in field implementation. Consequently, fundamental questions arise regarding the existing parking regulations in Yogyakarta and the urgency to harmonize parking fee regulations in the region. The objective of this research is to thoroughly examine the best approaches to harmonize the existing parking fee regulations in Yogyakarta. This step is taken with the ultimate goal of creating comprehensive regulations that are effective in implementation. Keywords: Parking, Local Regulations, Mayor Regulations